Béla Bartók : composition, concepts, and autograph sources - Somfai, László (Ernest Bloch lectures, 1996)
This long-awaited, authoritative account of Bartók's compositional processes stresses the composer's position as one of the masters of Western music history and avoids a purely theoretical approach or one that emphasizes him as an enthusiast for Hungarian folk music. For Bèla Bartók, composition often began with improvisation at the piano. Làszló Somfai maintains that Bartók composed without preconceived musical theories and refused.